The Role of the Despotess Irene Kantakouzene in the Political Life of the Serbian Despotate - Veselinović, Ivana D. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Despotess Irene was considered the second person of the Serbian despotate in Serbian historiography, but, thaks to Serbian and Byzantine sources that mention her actions, this paper attempts to answer the question of her joint rule with despot Djuradj Branković in Serbian state, as an independent political factor. The first example of this is Efsigmen charter from 1429, which the despot issues together with his wife. In addition, the miniature on Irene’s charter shows her with a scepter in her hand, a royal sign, althought her and Djuradj’s son have already been nominated for the heir to the throne, as indicated by the red shoes. Her activity is seen in the presence of a large number of Byzantines in Serbia, and than in the administration of the Serbian state. Of the Byzantines who lived inSerbia, the brother of the despotess Irene Toma Kantakouzene is very important, who became the commander of the Srrbian army, which is very unusual for the middle ages in Serbia.  During 1435, during Djuradj’s visit to Požun, Irene ruled the country as we know, based on the Dubrovnik mission she received. In addition, the despotess was a member of the state concil, and most likely the court council. Mavro Orbini left a note on her role in the diplomatic marriage between Mara Branković and Sultan Murad II, which Serbia used as means of preventing the Ottoman attack on the country. The fact that most points to Irene’s active political role is the question of the successor of the despot Djuradj. Mavro Orbini and Michael Kritovoulos wrote that Djuradj Branković appointed his wife to rule after his death, which is certainly related to the division in the family due to the deprivation of the throne of the blinded Grgur. Thuse, Irene would be a person around whome the family will gather and reconcile, and who will rule the country in which she already had experience. Her sudden death and the transfer of of part of the ruling family to Ottoman territory subsequently confirmed her right to power and the division that existed between Branković over the ruler and the country’s foreign policy.
Keywords: Irene Kantakouzenos; George Branković; Serbian despotate; Ottoman empire; foreign policy; Lordship of Serbian noble ladies